SIMULATION AND STRUCTURAL IMPROVEMENT DESIGN OF GEAR SYSTEM OF SHIFT ACTUATOR - ZHAO Xia; LIU XueWen (Jixie qiangdu)
Aiming at the phenomenon that the output gear of a shift actuator developed by an enterprise breaks in the working process, using the finite element analysis method to simulate the multi-body dynamics of the gear system. The stress distribution cloud diagram of the output gear and the output shaft during the movement shows that the maximum equivalent stress value of the output gear has exceeded the yield strength of the material, and the maximum equivalent stress value of the output shaft is close to the yield strength of the material. Improve the structural weaknesses of the output gear and output shaft, simulate the improved gear system and carry out the overload test to verify. The results show that the maximum stress value of the output gear and the output shaft is significantly reduced, which meets the strength requirements of the gear system and improves the reliability and safety of the shift actuator.